Analisis Pengaruh Penggunaan Media Audiovisual dalam Pembelajaran Bahasa Indonesia di SMP Swasta Idanoi - Zebua, Seruni Cerah; Gulo, Wenti Marlina; Lase, Rita Sujud Yanti; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
The author's purpose in conducting this research is to provide an understanding of the extent to which audiovisual media is effective in increasing students' understanding and involvement in Indonesian language learning. The method used in this study is a qualitative method with a descriptive approach. The subject of this study is Junior High School Class VII students. The data collection technique used by the researcher is in the form of a questionnaire. The analysis technique used is descriptive analysis that uses learning media in audiovisual form when delivering learning to students. The results of this study show that the use of audio-visual media in Indonesian language learning can significantly improve students' understanding